Addressing COVID-19 vaccine hesitancy in rural communities: A case study in engaging trusted messengers to pivot and plan - Reichelt, Melhaney; Cullen, John Patrick; Mayer-Fried, Sara; Russell, Holly Ann; Bennett, Nancy M.; Yousefi-Nooraie, Reza (Frontiers in Public Health, 2023)
The pandemic declaration of COVID-19 in 2020 presented unique challenges, lessons, and opportunities for public health practice in the United States. Despite clear evidence of COVID-19 vaccine effectiveness, vaccine uptake and vaccine confidence remained low in many regions. Vaccine holdouts, or those who are vaccine hesitant, have been an increasingly difficult population to reach. Several factors influence vaccine hesitancy and behavior in rural areas, including health care access challenges, misinformation, political loyalties, and concerns regarding the perceived lack of trustworthy evidence and knowledge of long-term effects. In March 2021, the Finger Lakes Rural Immunization Initiative (FLRII) engaged stakeholders to address vaccine hesitancy in a nine-county region of rural New York known as the Finger Lakes. Driven by data collected from community partners, physicians, and local health departments regarding their biggest barriers and greatest needs, the FLRII team created an interactive program for trusted messengers (TMs) including a stakeholder panel, called the Trusted Messenger Forum (TMF). The TMF met every 2 weeks from August 2021- August 2022 to engage local TMs and disseminate up-to-date knowledge in real time. During forum sessions, TMs shared detailed accounts of their experiences combating vaccine hesitancy in their communities and supported one another in their efforts through positive interaction and reaffirming conversations. Collaborations between community stakeholders can form a scaffolding to support a rapid response to a variety of public health problems and result in impactful change. For researchers implementing community-based research projects, modeling stakeholder panels after trusted messenger forums can be effective for diversifying the scope of the project and reacting to emergent problems in real-time.